Impact of the TRISO fuel homogenisation approximation in the MHTGR. (April 2023) - Golesorkhi, S.; Kelly, S.; Trottier, A.
Abstract: TRistructural ISOtropic (TRISO) fuels are commonly used in High-Temperature Gas cooled Reactors due to their resistance to high temperatures, irradiation, and oxidation. Reactor physics modelling of a fuel form consisting of millions of layered particles is quite challenging, however. Homogenisation techniques are often used to simplify the fuel form, representing it as a solid material to reduce computational costs. The impact of these approximations on reactor physics parameters was evaluated using OpenMC. Geometries at various scales (i.e. fuel pin, fuel block, full core) were developed based on the Modular High-Temperature Gas-cooled Reactor. It was found that homogenisation results in a significant reduction in simulation time. The Reactivity equivalent Physical Transformation (RPT) method was found to be superior to simple Volume-Weighted Homogenization (VWH). The neutron energy spectra and flux distributions calculated by RPT had insignificant differences to the explicit model. Reactivity coefficients were found to be similar, but diverged at very high temperatures. Highlights: Explicit neutronic modelling of TRISO particles is computationally expensive. Fuel homogenisation was studied using OpenMC models of the MHTGR benchmark. Reactor physics parameters of fuel pin, fuel block, and full core were compared. The RPT method was found to be an adequate approximation, greatly reducing run time.